Carbon material, method for producing carbon material, negative electrode, and secondary battery

By using carbon materials with specific specific surface area and curvature change rate, the shortcomings of lithium-ion secondary batteries in high-temperature storage recovery rate and discharge load characteristics are solved, and the battery performance is improved.

CN119630609APending Publication Date: 2025-03-14MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380057122.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-03
Filing Date
2023-06-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lithium-ion secondary batteries have shortcomings in the high-temperature storage recovery rate, and the specific surface area of ​​the negative electrode material increases during high-density pressing, which affects the battery performance.

Method used

Carbon materials that meet the specific specific surface area and curvature change rate are adopted, and the discharge load characteristics and high-temperature storage recovery rate of the secondary battery are ensured through reasonable carbon materials combination and manufacturing methods.

Benefits of technology

The high-temperature storage recovery rate and discharge load characteristics of the secondary battery are greatly improved, avoiding excessive increase in the specific surface area of ​​the plate, and improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259467890000251
    Figure BDA0005259467890000251
  • Figure BDA0005259467890000252
    Figure BDA0005259467890000252
  • Figure BDA0005259467890000253
    Figure BDA0005259467890000253
Patent Text Reader

Abstract

The present invention addresses the problem of providing a carbon material having excellent discharge load characteristics of a secondary battery and excellent high-temperature storage recovery rate of the secondary battery, and providing a method for producing a carbon material having excellent discharge load characteristics of a secondary battery and excellent high-temperature storage recovery rate of a secondary battery. The present invention relates to a carbon material satisfying the following formula (1) and formula (2), or a carbon material containing a carbon material (A) satisfying the following formula (3) and a carbon material (B) satisfying the following formula (4). 0.1 < = SAe / SAp < = 1.2 (1) 1 < = alpha < = 10 (2) 0.1 < = alpha < = 6 (3) 8 < = alpha 2 < = 20 (4)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon material, a method for producing the carbon material, a negative electrode and a secondary battery. Background Art

[0002] In recent years, with the miniaturization of electronic devices, the demand for high-capacity secondary batteries has gradually increased. In particular, compared with nickel-cadmium batteries and nickel-metal hydride batteries, secondary batteries with higher energy density and excellent charge and discharge characteristics, especially lithium-ion secondary batteries, have attracted attention. As lithium-ion secondary batteries, non-aqueous lithium secondary batteries consisting of positive and negative electrodes capable of absorbing / releasing lithium ions and non-aqueous electrolytes dissolved with lithium salts such as LiPF6 and LiBF4 have been developed and put into practical use.

[0003] In the past, extensive research has been conducted on improving the performance of lithium ion secondary batteries, but in recent years, further improvement in the performance of lithium ion secondary batteries has been required. For example, Patent Document 1 discloses a negative electrode material that improves the performance of a non-aqueous secondary battery by setting the pore volume to a specific range.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2020 / 196914 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] However, the negative electrode material disclosed in Patent Document 1 increases the specific surface area of ​​the electrode plate due to damage to the binder and active material particles when compacted to a high density, and thus the high-temperature storage recovery rate of the secondary battery is poor.

[0009] The present invention is completed in view of such technical problems, and the purpose of the present invention is to provide a carbon material having excellent discharge load characteristics of a secondary battery and a high temperature storage recovery rate of a secondary battery. In addition, the purpose of the present invention is to provide a method for manufacturing a carbon material having excellent discharge load characteristics of a secondary battery and a high temperature storage recovery rate of a secondary battery.

[0010] Means used to solve problems

[0011] In the past, various types of negative electrode materials have been studied, but no negative electrode material that can take into account both the discharge load characteristics of secondary batteries and the high temperature storage recovery rate of secondary batteries has been found. The present inventors have repeatedly conducted in-depth research to solve the above technical problems, and found that by using a carbon material that satisfies the two formulas described below, the discharge load characteristics of secondary batteries and the high temperature storage recovery rate of secondary batteries can be taken into account, thereby completing the present invention.

[0012] A first aspect of the present invention is a carbon material that satisfies the following formula (1) and the following formula (2).

[0013] 0.1≤SAe / SAp≤1.2 (1)

[0014] 1≤α≤10 (2)

[0015] (In formula (1), SAp is the specific surface area of ​​the powder form of the carbon material, and SAe is the specific surface area at the inflection point of the load-density when the carbon material is pressed into a plate. In formula (2), α is the specific surface area of ​​the carbon material at a pressed density of 1.3 g / cm 3 ~1.7g / cm 3 The rate of change of curvature within the range of .

[0016] Aspect 2 of the present invention is the carbon material according to aspect 1, wherein SAp is 1.5 m 2 / g~4.5m 2 / g.

[0017] A third aspect of the present invention is the carbon material according to the first or second aspect, wherein SAe is 0.5 m 2 / g~3.5m 2 / g.

[0018] A fourth aspect of the present invention is the carbon material according to any one of aspects 1 to 3, wherein the volume-based average particle size is 5 μm to 25 μm.

[0019] A fifth aspect of the present invention is a carbon material comprising a carbon material (A) satisfying the following formula (3) and a carbon material (B) satisfying the following formula (4).

[0020] 0.1≤α1≤6 (3)

[0021] 8≤α2≤20 (4)

[0022] (In formula (3), α1 is the carbon material at a compacted density of 1.3 g / cm 3 ~1.7g / cm 3 In formula (4), α2 is the change rate of curvature in the range of 1.3 g / cm 3 ~1.7g / cm 3 The rate of change of curvature within the range of .

[0023] Aspect 6 of the present invention is the carbon material according to aspect 5, wherein the ratio Rd50 of the volume-based average particle size of the carbon material (A) to the volume-based average particle size of the carbon material (B) is 0.3 to 1.6.

[0024] A seventh aspect of the present invention is the carbon material according to the fifth or sixth aspect, wherein a ratio RSAp of a specific surface area of ​​the carbon material (A) to a specific surface area of ​​the carbon material (B) is 2 to 15.

[0025] An eighth aspect of the present invention is the carbon material according to any one of the fifth to seventh aspects, wherein a ratio RTap of the tap density of the carbon material (A) to the tap density of the carbon material (B) is 0.7 to 1.4.

[0026] A ninth aspect of the present invention is the carbon material according to any one of the fifth to eighth aspects, wherein the content of the carbon material (A) is 50% to 95% by mass, and the content of the carbon material (B) is 5% to 50% by mass.

[0027] A tenth aspect of the present invention is the method for producing a carbon material according to any one of aspects 5 to 9, comprising the step of mixing the carbon material (A) and the carbon material (B).

[0028] Aspect 11 of the present invention is a negative electrode including a current collector and an active material layer formed on the current collector, wherein the active material layer includes the carbon material according to any one of aspects 1 to 9.

[0029] A twelfth aspect of the present invention is a secondary battery including a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode is the negative electrode according to the eleventh aspect.

[0030] Effects of the Invention

[0031] The carbon material of the present invention can achieve both the discharge load characteristics of the secondary battery and the high temperature storage recovery rate of the secondary battery by being used as an active material of the negative electrode of the secondary battery. In addition, the method for producing the carbon material of the present invention can obtain the carbon material. DETAILED DESCRIPTION

[0032] The present invention is described in detail below, but the present invention is not limited to the following embodiments and can be implemented with various modifications within the scope of the gist. It should be noted that in this specification, when an expression such as "to" is used, it is used as an expression including the numerical value or physical property value before and after it.

[0033] (Carbon material)

[0034] The carbon material of the present invention satisfies the following formula (1) and the following formula (2) in one embodiment.

[0035] 0.1≤SAe / SAp≤1.2 (1)

[0036] 1≤α≤10 (2)

[0037] In formula (1), SAp is the specific surface area of ​​the powder form of the carbon material, and SAe is the specific surface area at the inflection point of the load-density when the carbon material is pressed into a plate. In formula (2), α is the specific surface area of ​​the carbon material at a pressed density of 1.3 g / cm 3 ~1.7g / cm 3 The rate of change of curvature within the range of .

[0038] In this specification, the carbon material refers to a material composed of 90 mass % or more of carbon elements.

[0039] The carbon material of the present invention satisfies the above formulas (1) and (2), thereby ensuring a pore structure suitable for the movement of lithium ions when pressing the electrode plate and suppressing an excessive increase in the specific surface area of ​​the electrode plate, thereby being able to take into account both the discharge load characteristics of the secondary battery and the high-temperature storage recovery rate of the secondary battery.

[0040] From the perspective of suppressing side reactions with the electrolyte and having excellent high-temperature storage characteristics, the carbon material of the present invention preferably satisfies the following formula (1'), more preferably satisfies the following formula (1"), and even more preferably satisfies the following formula (1'").

[0041] 0.1≤SAe / SAp≤1.0 (1')

[0042] 0.4≤SAe / SAp≤0.95 (1”)

[0043] 0.6≤SAe / SAp≤0.9 (1”')

[0044] The powder specific surface area SAp of the carbon material of the present invention is preferably 1.5 m 2 / g or more, more preferably 2.0m 2 / g or more, preferably 4.5 m / g from the viewpoint of suppressing the increase of irreversible capacity and excellent initial charge and discharge efficiency. 2 / g or less, more preferably 4.0m 2 / g or less.

[0045] In this specification, the powder specific surface area SAp is a value measured by the BET method.

[0046] Specifically, using a specific surface area measuring device, the sample is pre-decompressed and dried at 350°C for 15 minutes under nitrogen flow, then cooled to liquid nitrogen temperature, and measured by the nitrogen adsorption BET single-point method based on the gas flow method using a nitrogen-helium mixed gas in which the relative pressure of nitrogen to atmospheric pressure is accurately adjusted to 0.3.

[0047] The specific surface area SAe of the carbon material of the present invention is preferably 0.5 m2 / g or more, more preferably 1.0 m 2 / g or more, preferably 3.5 m / g from the perspective of excellent initial charge and discharge efficiency and initial gas suppression. 2 / g or less, more preferably 3.0m 2 / g or less.

[0048] In this specification, the electrode plate specific surface area SAe is a value measured by the BET method.

[0049] Specifically, using a specific surface area measuring device, the sample is pre-decompressed and dried at 100°C for 30 minutes under nitrogen flow, then cooled to liquid nitrogen temperature, and measured by the nitrogen adsorption BET single-point method based on the gas flow method using a nitrogen-helium mixed gas in which the relative pressure of nitrogen to atmospheric pressure is accurately adjusted to 0.3.

[0050] From the viewpoint of maintaining an appropriate pore structure when pressed into an electrode plate and achieving excellent discharge load characteristics, the carbon material of the present invention preferably satisfies the following formula (2'), and more preferably satisfies the following formula (2").

[0051] 2≤α≤10 (2')

[0052] 3≤α≤10 (2”)

[0053] In this specification, the compacted density is 1.3 g / cm 3 ~1.7g / cm 3 The rate of change of curvature within the range is calculated based on the impedance response analysis.

[0054] The impedance response analysis was performed using an impedance analyzer at a frequency of 20 kHz to 10 mHz and a voltage amplitude of 10 mV. The ionic resistance R of the active material layer relative to the negative electrode sheet was obtained by using the intersection of a 45° straight line in the high-frequency region and a vertical line in the low-frequency region on the Kerr plot. ion The curvature is calculated according to the following formula (5) where the area of ​​the negative electrode sheet is S, the thickness of the active material layer of the negative electrode sheet is L, the conductivity of the electrolyte is σ, and the porosity of the active material layer is ε.

[0055] Curvature = R ion ×(ε / 2×L)×(σ×S) (5)

[0056] Using the calculated curvature, the compacted density is calculated according to the following formula (6): 3 ~1.7g / cm 3 The rate of change of curvature within the range of .

[0057] [Rate of change in curvature] = [Change in curvature] / [Change in pressing density] (6)

[0058] As for the volume-based average particle size d50 of the carbon material of the present invention, from the perspective of suppressing excessive reaction with the electrolyte and excellent initial charge and discharge efficiency, it is preferably 5 μm or more, more preferably 8 μm or more, and further preferably 10 μm or more. From the perspective of suppressing the generation of stripes during polarization, it is preferably 25 μm or less, more preferably 22 μm or less, and further preferably 20 μm or less.

[0059] In this specification, the volume-based average particle diameter d50 is a volume-based median particle diameter value measured by a laser diffraction / scattering particle size distribution analyzer.

[0060] Specifically, 0.01 g of a sample is suspended in 10 mL of a 0.2% by mass aqueous solution of polyoxyethylene sorbitan monolaurate as a surfactant, introduced into a laser diffraction / scattering particle size distribution analyzer, and irradiated with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, and then the volume-based median particle size in the above-mentioned measuring device is measured.

[0061] The tap density of the carbon material of the present invention is preferably 0.70 g / cm2 from the viewpoints of suppressing process defects such as streaks during plate production, easily forming a negative electrode sheet with good rolling properties and high density due to improved filling properties, reducing the curvature of the lithium ion migration path when the plate is made, and improving the rapid charge and discharge properties by smoothing the movement of the electrolyte due to the neat shape of the gaps between the particles. 3 More preferably 0.80 g / cm 3 More preferably, 0.90 g / cm 3 The above is preferably 1.40 g / cm2 because the particles have appropriate space on the surface or inside and the particles do not become too hard, thereby having excellent plate compressibility, rapid charge and discharge characteristics, and excellent low-temperature input and output characteristics. 3 Below, more preferably 1.30 g / cm 3 Below, more preferably 1.10 g / cm 3 the following.

[0062] In this specification, the tap density is measured by using a powder density tester to drop the sample to a diameter of 1.6 cm and a volume of 20 cm. 3 A cylindrical vibration container is placed in the container. After the container is filled, 1000 vibrations are performed with a stroke length of 10 mm. The density value is calculated based on the volume and mass of the sample at this time.

[0063] With regard to the roundness of the carbon material of the present invention, from the perspective of reducing the curvature of lithium ion diffusion, smoothing the movement of the electrolyte into the gaps between the particles, and excellent rapid charge and discharge characteristics, the roundness is preferably 0.88 or more, more preferably 0.90 or more, and further preferably 0.92 or more. From the perspective of ensuring the contact between carbon materials and excellent cycle characteristics, the roundness is preferably 0.99 or less, more preferably 0.98 or less, and further preferably 0.97 or less.

[0064] In this specification, the circularity is calculated by measuring the particle size distribution of the equivalent circle diameter by flow particle image analysis and by the following formula (9).

[0065] Specifically, ion exchange water is used as a dispersion medium, polyoxyethylene sorbitan monolaurate is used as a surfactant, and the dispersion is dispersed by ultrasound to obtain a dispersion liquid. Then, the shape of the particles is photographed using a flow image analysis device. Based on the images obtained by photographing at least 1,000 particles, the roundness of particles in the range of 1.5 μm to 40 μm in equivalent circle diameter is averaged as the roundness.

[0066] [Circularity] = [Circumference of an equivalent circle with the same area as the particle's projected shape] / [Actual circumference of the particle's projected shape] (9)

[0067] As for the cumulative pore volume of the carbon material of the present invention, considering the ease of deformation when moderately pressed, it is preferably 0.003 mL / g or more, more preferably 0.005 mL / g or more, further preferably 0.010 mL / g or more, preferably 0.120 mL / g or less, more preferably 0.090 mL / g or less, and further preferably 0.070 mL / g or less.

[0068] In this specification, the cumulative pore volume in the range of pore diameters of 0.01 μm or more and 1 μm or less is a value measured by mercury porosimetry using a mercury intrusion instrument.

[0069] Specifically, a mercury intrusion instrument is used to weigh the carbon material to a value of about 0.2 g, seal it in a powder container, degas for 10 minutes at 25°C and below 50μmHg, and perform pretreatment. Next, the pressure is reduced to 4psia, and mercury is introduced into the above container, and the pressure is increased from 4psia to 40000psia in stages, and then reduced to 25psia. The number of stages during the pressure increase is set to 80 points or more, and the amount of mercury intrusion is measured after a 10-second equilibrium time in each stage. The pore distribution is calculated using the Washburn equation based on the mercury intrusion curve obtained thereby. The surface tension (γ) of mercury is 485dyne / cm and the contact angle (θ) is 140° for calculation. The cumulative pore volume in the range of pore diameters above 0.01μm and below 1μm is calculated based on the obtained pore distribution.

[0070] As for the d10 of the carbon material of the present invention, from the perspective of suppressing the aggregation tendency of particles, slurry stability or excellent plate strength, it is preferably greater than 1 μm, more preferably greater than 3 μm, and further preferably greater than 5 μm. From the perspective of suppressing the generation of streaks during plate formation, it is preferably less than 30 μm, more preferably less than 20 μm, and further preferably less than 17 μm.

[0071] In this specification, d10 is a value at which the frequency % of particles from the smallest particle size accumulates to 10% in the particle size distribution obtained when the volume-based average particle size d50 is measured.

[0072] As for the d90 of the carbon material of the present invention, from the perspective of being able to suppress the reduction in the strength of the electrode plate, it is preferably greater than 20 μm, more preferably greater than 25 μm, and further preferably greater than 30 μm. From the perspective of suppressing the generation of streaks during electrode formation, it is preferably less than 100 μm, more preferably less than 70 μm, and further preferably less than 50 μm.

[0073] In this specification, d90 is a value at which the frequency % of particles from the smallest particle size reaches 90% in the particle size distribution obtained when the volume-based average particle size d50 is measured.

[0074] As for the DBP (dibutyl phthalate) oil absorption of the carbon material of the present invention, from the perspective of avoiding the reduction of the reaction surface by the presence of appropriate intra-particle voids, it is preferably 20 mL / 100 g or more, more preferably 30 mL / 100 g or more, and further preferably 40 mL / 100 g or more. From the perspective of suppressing the generation of streaks during polarization, it is preferably 85 mL / 100 g or less, more preferably 70 mL / 100 g or less, and further preferably 65 mL / 100 g or less.

[0075] In this specification, the DBP oil absorption is a value measured in accordance with ISO 4546.

[0076] Specifically, the DBP oil absorption is a value obtained by adding 40 g of a sample at a dropping rate of 4 mL / min, a rotation speed of 125 rpm, and a set torque of 500 N·m. Examples of the measuring device include an oil absorption meter type E manufactured by Brabender.

[0077] As another embodiment, the carbon material of the present invention includes a carbon material (A) satisfying the following formula (3) and a carbon material (B) satisfying the following formula (4).

[0078] 0.1≤α1≤6 (3)

[0079] 8≤α2≤20 (4)

[0080] In formula (3), α1 is the carbon material at a compacted density of 1.3 g / cm 3 ~1.7g / cm 3 In formula (4), α2 is the change rate of curvature in the range of 1.3 g / cm 3 ~1.7g / cm 3 The rate of change of curvature within the range of .

[0081] The carbon material of the present invention easily satisfies the above formula (1) and the above formula (2) by including the carbon material (A) satisfying the above formula (3) and the carbon material (B) satisfying the above formula (4).

[0082] (Carbon material (A))

[0083] The carbon material (A) satisfies the following formula (3).

[0084] 0.1≤α1≤6 (3)

[0085] The carbon material of the present invention contains the carbon material (A), which plays a role in maintaining the void structure when pressing the electrode plate, and has excellent lithium ion diffusibility.

[0086] From the viewpoint of suppressing excessive load when pressing the electrode plate, the carbon material (A) preferably satisfies the following formula (3'), and more preferably satisfies the following formula (3").

[0087] 0.5≤α1≤5.5 (3')

[0088] 1≤α1≤5 (3”)

[0089] The powder specific surface area SAp of the carbon material (A) is preferably 0.3 m / s from the viewpoint of ensuring a location for lithium to enter and exit and excellent rapid charge and discharge characteristics. 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 0.8m 2 / g or more, preferably 8.0 m / g from the perspective of suppressing the side reaction with the electrolyte and excellent initial charge and discharge efficiency 2 / g or less, more preferably 5.0m 2 / g or less, more preferably 2.5m 2 / g or less.

[0090] The tap density of the carbon material (A) is preferably 0.60 g / cm2 from the viewpoint of excellent packing properties when formed into an electrode plate. 3 More preferably 0.80 g / cm 3 More preferably, 1.00 g / cm 3 From the perspective of excellent conductivity between particles, the preferred value is 1.40 g / cm3 Below, more preferably 1.35g / cm 3 Below, more preferably 1.30 g / cm 3 the following.

[0091] As for the volume-based average particle size d50 of the carbon material (A), from the perspective of suppressing excessive reaction with the electrolyte and excellent initial charge and discharge efficiency, it is preferably greater than 1 μm, more preferably greater than 5 μm, and further preferably greater than 10 μm. From the perspective of suppressing the generation of stripes during polarization, it is preferably less than 40 μm, more preferably less than 30 μm, and further preferably less than 20 μm.

[0092] As for the roundness of the carbon material (A), from the perspective of ensuring the migration path of lithium ions in the electrolyte when the electrode is made and excellent high current density charge and discharge characteristics, it is preferably 0.88 or more, more preferably 0.90 or more, and further preferably 0.92 or more. From the perspective of ensuring the contact area between particles and excellent conductivity, it is preferably 0.99 or less, more preferably 0.98 or less, and further preferably 0.97 or less.

[0093] From the viewpoint that graphite is highly crystalline and has sufficient charge and discharge capacity, the d002 value of the carbon material (A) is preferably The following are more preferably The theoretical d002 value of graphite is The d002 value of natural graphite with high crystallinity shows a value close to the theoretical value. On the other hand, the d002 value of artificial graphite varies greatly depending on the type of raw material coke and the graphitization temperature.

[0094] From the viewpoint that graphite is highly crystalline and has sufficient charge and discharge capacity, the Lc of the carbon material (A) is preferably More preferably above.

[0095] In this specification, d002 value is the value of the interplanar spacing of the lattice plane (002 plane) measured by X-ray diffraction method using Gakushin method, and Lc is the value of the crystallite size measured by X-ray diffraction method using Gakushin method. The measurement conditions of X-ray diffraction are as follows.

[0096] Sample: A sample obtained by adding and mixing X-ray standard high-purity silicon powder in an amount of about 15% by mass of the total amount of the object to be measured.

[0097] X-ray: CuKα ray

[0098] Measuring range: 20°≤2θ≤30°

[0099] Step angle: 0.013°

[0100] Sample adjustment: Fill the concave part of the sample plate with a depth of 0.2 mm with powder sample to make a flat sample surface.

[0101] As for the Raman R value of the carbon material (A), it is preferably greater than 0.10, more preferably greater than 0.15, and further preferably greater than 0.20, from the perspective of preventing crystals from being oriented in the plane direction when the density is high and avoiding a decrease in the charge and discharge load characteristics. From the perspective of inhibiting excessive reaction with the electrolyte, avoiding a decrease in the charge and discharge efficiency and an increase in gas generation, it is preferably less than 0.80, more preferably less than 0.70, and further preferably less than 0.60.

[0102] In this specification, the Raman R value is the value obtained by measuring the Raman spectrum at 1580 cm -1 Nearby peaks P A Strength I A and 1360cm -1 Nearby peaks P B Strength I B , with its intensity ratio (I B / I A ) is calculated in the form of

[0103] In this manual, "1580cm -1 "Nearby" refers to 1580cm -1 ~1620cm -1 Range, "1360cm -1 "Nearby" refers to 1350cm -1 ~1370cm -1 range.

[0104] The Raman spectrum was measured using a Raman spectrometer. Specifically, the carbon material was naturally dropped into a measuring cell, and the cell was irradiated with an argon ion laser while being rotated in a plane perpendicular to the laser. The measurement conditions were as follows.

[0105] Wavelength of argon ion laser: 514.5nm

[0106] Laser power on sample: 25mW

[0107] Resolution: 4cm -1

[0108] Measuring range: 1100cm -1 ~1730cm -1

[0109] Peak intensity measurement, half peak width measurement: background processing, smoothing processing (by convolution of 5 points with simple average)

[0110] From the perspective of excellent lithium ion acceptance, the carbon material (A) is preferably graphite having a coating on at least a portion of its surface, more preferably graphite having a carbonaceous substance on at least a portion of its surface, and further preferably graphite having an amorphous carbonaceous substance on at least a portion of its surface.

[0111] As for the content rate of amorphous carbonaceous substances in carbon material (A), in 100 mass % of carbon material (A), from the aspect of obtaining a more uniform coating state and excellent charging acceptance, it is preferably 0.1 mass % or more, more preferably 1 mass % or more, and further preferably 3 mass % or more, and from the aspect of excellent rolling properties during pole plate formation, it is preferably 30 mass % or less, more preferably 20 mass % or less, and further preferably 15 mass % or less.

[0112] In this specification, the content of amorphous carbonaceous substance in carbon material is calculated by the following formula (10). That is, it is calculated based on the mass of carbon material and amorphous carbonaceous substance before and after firing. At this time, it is calculated assuming that there is no mass change before and after firing of carbon material.

[0113] Content of amorphous carbonaceous material (mass %) = [(mass of carbonaceous material containing amorphous carbonaceous material after firing - mass of carbonaceous material before firing) / mass of carbonaceous material before firing] × 100 (10)

[0114] (Method for producing carbon material (A))

[0115] The method for producing the carbon material (A) is not particularly limited as long as it can be produced in a manner that satisfies the above formula (3), but from the perspective of high capacity and excellent input-output characteristics and cycle characteristics, it is preferred to spheronize and pressurize the carbon material raw material in the presence of a granulating agent to attach an amorphous carbon precursor. Specifically, a production method comprising the following steps (1) to (6) is preferred.

[0116] Step (1): A step of adjusting the particle size of the carbon material raw material.

[0117] Step (2): A step of mixing the carbon material raw material and the granulating agent.

[0118] Step (3): a step of spheroidizing the carbon material raw material.

[0119] Step (4): a step of removing the granulating agent.

[0120] Step (5): pressure treatment step.

[0121] Step (6): a step of adding an amorphous carbonaceous material.

[0122] Hereinafter, steps (1) to (6) will be described, but steps other than steps (1) to (6) may be included, and the production method is not limited to the production method including steps (1) to (6).

[0123] (Process (1))

[0124] Step (1) is a step of adjusting the particle size of the carbon material raw material.

[0125] The carbon material raw material is preferably graphite, and natural graphite and artificial graphite are more preferred from the perspective of high crystallinity and excellent capacity. Natural graphite is further preferred from the perspective of higher crystallinity, better capacity, and no need for heat treatment during production. Graphite is preferably graphite with few impurities, and is more preferably used after purification treatment as needed.

[0126] Examples of natural graphite include earthy graphite, scaly graphite, and flaky graphite. Among these natural graphites, scaly graphite and flaky graphite are preferred, and flaky graphite is more preferred, from the viewpoint of high graphitization degree and small amount of impurities.

[0127] As artificial graphite, for example, there can be listed substances obtained by heating organic substances such as coal tar pitch, coal-based heavy oil, atmospheric residue, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymers, polyphenylene sulfide, polyphenylene ether, furfuryl alcohol resin, phenol formaldehyde resin, and imide resin to 2500° C. or above for graphitization.

[0128] From the viewpoint that graphite is highly crystalline and has sufficient charge and discharge capacity, the d002 value of the carbon material raw material is preferably The following are more preferably the following.

[0129] From the viewpoint that graphite is highly crystalline and has sufficient charge and discharge capacity, the Lc of the carbon material raw material is preferably More preferably above.

[0130] From the viewpoint of excellent capacity and battery safety, the purity of the carbon material raw material is preferably 99.0% or more, more preferably 99.5% or more, further preferably 99.9% or more, and particularly preferably 100%.

[0131] In this specification, the purity is a value calculated from the mass of the carbon material raw material before and after heating by accurately weighing about 10 g of the carbon material raw material after sufficient drying and heating it at 815° C. in the atmosphere for 10 hours.

[0132] As for the volume-based average particle size (d50) of the carbon material raw material, from the perspective of excellent transportability, it is preferably greater than 1 μm, more preferably greater than 3 μm, and further preferably greater than 5 μm. From the perspective of excellent productivity, it is preferably less than 150 μm, more preferably less than 130 μm, and further preferably less than 120 μm.

[0133] The specific surface area (SA) of the carbon material raw material is preferably 1.0 m 2 / g or more, more preferably 1.5m 2 / g or more, more preferably 2.0m 2 / g or more, preferably 30.0 m / g from the viewpoint of excellent control of irreversible capacity 2 / g or less, more preferably 20.0m 2 / g or less, more preferably 10.0 m 2 / g or less.

[0134] The tap density of the carbon material raw material is preferably 0.60 g / cm 3 More preferably, 0.70 g / cm 3 More preferably, 0.80 g / cm 3 From the perspective of easy control during pulverization, 1.40 g / cm 3 Below, more preferably 1.30 g / cm 3 Below, more preferably 1.20 g / cm 3 the following.

[0135] As for the Raman R value of the carbon material raw material, it is preferably above 0.10, more preferably above 0.15, and further preferably above 0.20, from the perspective of preventing the crystals from being oriented in the plane direction under high density and avoiding the reduction of the charge and discharge load characteristics. From the perspective of inhibiting excessive reaction with the electrolyte, avoiding the reduction of the charge and discharge efficiency and the increase of gas generation, it is preferably below 0.80, more preferably below 0.70, and further preferably below 0.60.

[0136] The method for adjusting the particle size of the carbon material raw material is not particularly limited as long as it can be adjusted to the volume-based average particle size and specific surface area described below, and pulverization, crushing, or classification may be performed.

[0137] A known method can be used for pulverization, crushing and classification.

[0138] From the perspective of easy control of spheroidization treatment, the volume-based average particle size (d50) of the carbon material raw material after particle size adjustment is preferably greater than 1 μm, more preferably greater than 2 μm, further preferably greater than 3 μm, preferably less than 20 μm, more preferably less than 15 μm, and further preferably less than 12 μm.

[0139] The specific surface area (SA) of the carbon material raw material after particle size adjustment is preferably 5.0 m 2 / g or more, more preferably 7.5m 2 / g or more, more preferably 10.0 m 2 / g or more, preferably 30.0 m / g from the perspective of suppressing the side reaction with the electrolyte, preventing the decrease in initial charge and discharge efficiency, the increase in gas generation, and the improvement of battery capacity. 2 / g or less, more preferably 25.0m 2 / g or less, more preferably 20.0m 2 / g or less.

[0140] From the viewpoint of excellent spheroidization degree during spheroidization, the tap density of the carbon material raw material after particle size adjustment is preferably 0.60 g / cm 3 More preferably, 0.70 g / cm 3 More preferably, 0.80 g / cm 3 Above, preferably 1.40 g / cm 3 Below, more preferably 1.30 g / cm 3 Below, more preferably 1.20 g / cm 3 the following.

[0141] (Process (2))

[0142] Step (2) is a step of mixing the carbon material raw material and the granulating agent.

[0143] The granulating agent is preferably liquid when the carbon material raw material is spheronized.

[0144] Furthermore, the granulating agent preferably contains an organic compound that becomes amorphous carbon.

[0145] Furthermore, the granulating agent is preferably a granulating agent not containing an organic solvent, a granulating agent containing an organic solvent and at least one of the organic solvents having no flash point, or a granulating agent containing an organic solvent and having a flash point of 5° C. or higher.

[0146] When the granulating agent meets the above necessary conditions, when the carbon material raw materials are spheroidized, the granulating agent becomes a liquid bridge between the carbon material raw materials, and the capillary negative pressure of the liquid bridge and the surface tension of the liquid between the carbon material raw materials generate gravity, which can effectively shorten the distance between the carbon material raw materials.

[0147] As a method for mixing the carbon material raw material and the granulating agent, for example, there can be cited a method of mixing the carbon material raw material and the granulating agent using a mixer or a kneader, a method of adding the carbon material raw material to a solution in which the granulating agent is dissolved and removing the solvent, etc. Among these methods, the method of mixing the carbon material raw material and the granulating agent using a mixer or a kneader is preferred from the perspective of being able to effectively reduce micropores of 1 nm to 4 nm.

[0148] From the perspective of being able to suppress the reduction in sphericity caused by the reduction in adhesion between carbon material raw materials and the reduction in productivity caused by the adhesion of carbon material raw materials to the device, the amount of granulating agent added is preferably 0.1 mass part or more, more preferably 1 mass part or more, further preferably 10 mass parts or more, preferably 1000 mass parts or less, more preferably 100 mass parts or less, and further preferably 50 mass parts or less, relative to 100 mass parts of carbon material raw materials.

[0149] (Process (3))

[0150] Step (3) is a step of spheronizing the carbon material raw material.

[0151] By spheroidizing the carbon material raw material, it has excellent rapid charge and discharge characteristics.

[0152] As a method for spheronizing the carbon material raw material, a method of spheronizing the carbon material raw material by applying mechanical energy is preferred because the shape of particles can be easily controlled.

[0153] Examples of the mechanical energy include impact, compression, friction, shear force, etc. These mechanical energies may be used alone or in combination of two or more.

[0154] The method of spheroidizing the carbon material raw material by applying mechanical energy may use only a device that applies mechanical energy.

[0155] The viscosity of the granulating agent when the carbon material raw material is spheroidized is preferably 1 cP or more, more preferably 5 cP or more, further preferably 10 cP or more, particularly preferably 20 cP or more, preferably 1000 cP or less, more preferably 800 cP or less, further preferably 600 cP or less, and particularly preferably 500 cP or less, from the perspectives of being able to suppress re-detachment from the spheroidized particles caused by the impact force with the rotor or the shell during the spheroidization treatment, being able to reduce the micropores due to the granulating agent entering the micropores of 1 nm to 4 nm to become amorphous carbon, and having excellent low-temperature input-output characteristics or high-temperature storage characteristics.

[0156] The viscosity of the granulating agent when the carbon material raw material is spheronized can be adjusted by the amount of the organic solvent and the temperature of the spheronization treatment.

[0157] In this specification, viscosity is a value measured at 25°C using a rheometer. -1 When the shear stress is 0.1Pa or more, the shear rate is 100s -1 The value measured at a shear rate of 100 s -1 When the shear stress is less than 0.1Pa, the -1 The value measured at a shear rate of 1000s -1 When the shear stress is less than 0.1 Pa, it is a value measured at a shear rate at which the shear stress is 0.1 Pa or more.

[0158] When the carbon material raw material is spheroidized, the carbon material raw material may be granulated in the presence of other substances. Examples of other substances include metals capable of alloying with lithium, oxides thereof, amorphous carbon, raw coke, and the like.

[0159] When the carbon material raw material is spheroidized, it is preferred to attach the fine powder generated in the spheroidization process to the surface of the carbon material while spheroidizing. By attaching the fine powder generated in the spheroidization process to the surface of the carbon material while spheroidizing, when the carbon material is coated with an amorphous carbonaceous material or a graphite material, the voids in the carbon material can be effectively reduced. In addition, the amount of the edge that can be used as the insertion and separation site of lithium ions increases, so that the electrolyte is effectively distributed throughout the voids in the carbon material, and the low temperature input and output characteristics and cycle characteristics are excellent.

[0160] The fine powder is not limited to the fine powder generated in the spheroidization treatment, and fine powder having a particle size adjusted may be separately added.

[0161] In order to make the fine powder adhere effectively to the surface of the carbon material, it is preferable to enhance the adhesion between carbon material particles, between carbon material particles and fine powder particles, and between fine powder particles and fine powder particles.

[0162] Examples of the adhesion force between particles include van der Waals force not via interparticle inclusions, electrostatic attraction, physical crosslinking force via interparticle inclusions, and chemical crosslinking force.

[0163] The van der Waals force is bounded by a volume-based average particle size (d50) of 100 μm, and the smaller the particle size, the more [self-weight] < [adhesion]. Therefore, the smaller the volume-based average particle size of the carbon material raw material, the stronger the adhesion between the particles, and the easier it is for the fine powder to adhere to the carbon material and the fine powder to be enclosed in the spherical carbon material, so it is preferred.

[0164] Alternatively, the carbon material raw material and the granulating agent may be placed in a spheronization treatment apparatus and the steps (2) and (3) may be performed simultaneously.

[0165] (Process (4))

[0166] Step (4) is a step of removing the granulating agent.

[0167] The granulating agent may be removed in whole or in part.

[0168] When a granulating agent containing an organic solvent is used, it is preferred to remove the organic solvent as well.

[0169] As a method for removing the granulating agent and the organic solvent, for example, there can be cited a method of washing with a solvent, a method of volatilizing / decomposing by heating, etc. Among these methods, the method of volatilizing / decomposing by heating is preferred from the viewpoint of excellent productivity and removal efficiency.

[0170] (Process (5))

[0171] Step (5) is a step of performing a pressure treatment.

[0172] Examples of the pressurization treatment include isotropic pressurization and anisotropic pressurization. Among these pressurization treatments, isotropic pressurization is preferred because it can be controlled to satisfy the formula (3).

[0173] Examples of the pressurization method include hydrostatic isotropic pressurization using water as the pressurization medium, isotropic pressurization using gas such as air as the pressurization medium, and pressurization in a mold by uniaxial pressing and pressurization in a constant direction.

[0174] From the perspective of easy control to satisfy formula (3), the pressurized pressure is preferably 50 MPa or more, more preferably 100 MPa or more, and further preferably 150 MPa or more, and is preferably 300 MPa or less, more preferably 280 MPa or less, and further preferably 260 MPa or less.

[0175] Step (5) may be performed at any time during steps (1) to (6), but is preferably performed between steps (4) and (6) from the viewpoint of efficiently applying pressure while removing excess granulating agent.

[0176] (Process (6))

[0177] Step (6) is a step of adding an amorphous carbonaceous substance.

[0178] By adding amorphous carbonaceous substances to the carbon material, the side reaction between the negative electrode and the electrolyte can be suppressed, resulting in high capacity, excellent low-temperature input-output characteristics, and high-temperature storage characteristics.

[0179] The amorphous carbonaceous material refers to carbon having a d002 value of 0.340 nm or more.

[0180] From the perspective of suppressing excessive side reactions with the electrolyte and excellent initial charge and discharge efficiency, the method of adding amorphous carbonaceous substances to the carbon material is preferably: the carbon material and the amorphous carbonaceous substance precursor are mixed, heated in a non-oxidizing atmosphere, and the amorphous carbonaceous substance precursor is amorphously carbonized.

[0181] As a method for mixing a carbon material and an amorphous carbonaceous substance precursor, for example, a method of mixing a carbon material and an amorphous carbonaceous substance precursor using a mixer or a kneader, a method of adding a carbon material to a solution in which an amorphous carbonaceous substance precursor is dissolved and removing a solvent, etc. Among these methods, a method of mixing a carbon material and an amorphous carbonaceous substance precursor using a mixer or a kneader is preferred from the perspective of being able to effectively reduce micropores of 1 nm to 4 nm.

[0182] The atmosphere during heating is not particularly limited as long as it is a non-oxidizing atmosphere, but is preferably a nitrogen, argon or carbon dioxide atmosphere, and more preferably a nitrogen atmosphere, from the viewpoint of suppressing the generation of micropores due to oxidation.

[0183] From the viewpoint of easiness of control so as to satisfy the formula (3), the oxygen concentration is preferably 1 vol% or less, and more preferably 0.1 vol% or less.

[0184] The heating temperature for amorphous carbonaceous material precursor carbonization is not particularly limited as long as it does not reach a crystal structure equivalent to the crystal structure of graphite, but is preferably 500°C or higher, more preferably 600°C or higher, further preferably 700°C or higher, preferably 2000°C or lower, more preferably 1800°C or lower, and further preferably 1600°C or lower.

[0185] From the viewpoint of easy control so as to satisfy the formula (3), the heating time is preferably 0.1 hour or longer, more preferably 1 hour or longer, and is preferably 1000 hours or shorter, more preferably 100 hours or shorter.

[0186] As amorphous carbonaceous material precursors, for example, aromatic hydrocarbons such as tar, pitch, naphthalene, anthracene, phenolic resins, thermoplastic resins such as polyvinyl alcohol resins, etc. can be listed. These precursors can be used alone or in combination of two or more. Among these precursors, tar, pitch, and aromatic hydrocarbons are preferred from the perspective of easy development of carbon structure and ability to be coated with a small amount. From the perspective of easy control to satisfy formula (3), substances with a residual carbon rate of 50% or more are more preferred, and substances with a residual carbon rate of 60% or more are further preferred.

[0187] From the perspective of easy control to satisfy formula (3), the ash content in the amorphous carbonaceous material precursor is preferably 0.00001 mass % or more, preferably 1 mass % or less, more preferably 0.5 mass % or less, and further preferably 0.1 mass % or less in 100 mass % of the amorphous carbonaceous material precursor.

[0188] From the perspective of easily controlling to satisfy formula (3), the metal impurity content in the amorphous carbonaceous material precursor is preferably 0.1 mass ppm or more, preferably 1000 mass ppm or less, more preferably 500 mass ppm or less, and further preferably 100 mass ppm or less.

[0189] In this specification, the metal impurity content is a value obtained by dividing the total content of Fe, Al, Si, and Ca in the amorphous carbonaceous material precursor by the residual carbon ratio.

[0190] From the viewpoint of easily controlling to satisfy the formula (3), the Qi (quinoline insoluble component) in the amorphous carbonaceous material precursor is preferably 5 mass % or less, more preferably 3 mass % or less in 100 mass % of the amorphous carbonaceous material precursor.

[0191] In order to adjust the volume-based average particle size of the carbon material (A) to a desired range, the carbon material obtained through the steps (1) to (6) may be pulverized, crushed, or classified as necessary.

[0192] A known method can be used for pulverization, crushing and classification.

[0193] As for the content rate of the amorphous carbonaceous material precursor in the mixture of carbon material and amorphous carbonaceous material precursor, in 100 mass % of the mixture of carbon material and amorphous carbonaceous material precursor, from the aspect of obtaining a more uniform coating state and excellent charging acceptance, it is preferably 0.1 mass % or more, more preferably 1 mass % or more, and further preferably 3 mass % or more, from the aspect of excellent rolling property during pole plate formation, it is preferably 30 mass % or less, more preferably 20 mass % or less, and further preferably 15 mass % or less.

[0194] (Carbon material (B))

[0195] The carbon material (B) satisfies the following formula (4).

[0196] 8≤α2≤20 (4)

[0197] The carbon material of the present invention contains the carbon material (B), thereby improving the rolling properties during plate pressing, dispersing the load applied to particles in the plate, suppressing the increase in the specific surface area of ​​the plate, and achieving excellent high-temperature storage characteristics.

[0198] From the viewpoint of suppressing excessive particle deformation and excelling in lithium ion diffusibility, the carbon material (B) preferably satisfies the following formula (4'), and more preferably satisfies the following formula (4").

[0199] 9≤α2≤19 (4')

[0200] 10≤α2≤18 (4”)

[0201] The powder specific surface area SAp of the carbon material (B) is preferably 3.0 m 2 / g or more, more preferably 4.0m 2 / g or more, more preferably 5.0m 2 / g or more, preferably 20.0 m / g from the perspective of suppressing the side reaction with the electrolyte and excellent initial charge and discharge efficiency 2 / g or less, more preferably 15.0m 2 / g or less, more preferably 10.0 m 2 / g or less.

[0202] The tap density of the carbon material (B) is preferably 0.70 g / cm2 from the viewpoint of excellent packing properties when formed into an electrode plate. 3 More preferably, 0.75 g / cm 3 More preferably, 0.80 g / cm 3 From the perspective of excellent conductivity between particles, 1.30 g / cm 3 Below, more preferably 1.20 g / cm 3 Below, more preferably 1.10 g / cm 3 the following.

[0203] As for the volume-based average particle size d50 of the carbon material (B), from the perspective of suppressing excessive reaction with the electrolyte and excellent initial charge and discharge efficiency, it is preferably greater than 1 μm, more preferably greater than 5 μm, and further preferably greater than 10 μm. From the perspective of suppressing the generation of stripes during polarization, it is preferably less than 40 μm, more preferably less than 30 μm, and further preferably less than 20 μm.

[0204] As for the roundness of the carbon material (B), from the perspective of ensuring the migration path of lithium ions in the electrolyte when the electrode is made and excellent high current density charge and discharge characteristics, it is preferably 0.88 or more, more preferably 0.90 or more, and further preferably 0.92 or more. From the perspective of ensuring the contact area between particles and excellent conductivity, it is preferably 0.99 or less, more preferably 0.98 or less, and further preferably 0.97 or less.

[0205] From the viewpoint that graphite is highly crystalline and has sufficient charge and discharge capacity, the d002 value of the carbon material (B) is preferably The following are more preferably The theoretical d002 value of graphite is The d002 value of natural graphite with high crystallinity shows a value close to the theoretical value. On the other hand, the d002 value of artificial graphite varies greatly depending on the type of raw material coke and the graphitization temperature.

[0206] From the viewpoint that graphite is highly crystalline and has sufficient charge and discharge capacity, the Lc of the carbon material (B) is preferably More preferably above.

[0207] As for the Raman R value of the carbon material (B), it is preferably greater than 0.10, more preferably greater than 0.15, and further preferably greater than 0.20, from the perspective of preventing crystals from being oriented in the plane direction when the density is high and avoiding a decrease in the charge and discharge load characteristics. From the perspective of inhibiting excessive reaction with the electrolyte, avoiding a decrease in the charge and discharge efficiency and an increase in gas generation, it is preferably less than 0.80, more preferably less than 0.70, and further preferably less than 0.60.

[0208] (Method for producing carbon material (B))

[0209] The method for producing the carbon material (B) is not particularly limited as long as it can be produced in a manner that satisfies the above formula (4), but from the perspective of good filling properties and excellent capacity as an electrode plate, it is preferred to use spherical flake natural graphite as the carbon material (B).

[0210] The raw material of the carbon material (B) is preferably graphite, and natural graphite and artificial graphite are more preferred from the perspective of high crystallinity and excellent capacity. Natural graphite is further preferred from the perspective of higher crystallinity, better capacity, and no need for heat treatment during production. Graphite is preferably graphite with few impurities, and is more preferably used after purification treatment as needed.

[0211] Examples of natural graphite include earthy graphite, scaly graphite, and flaky graphite. Among these natural graphites, scaly graphite and flaky graphite are preferred, and flaky graphite is more preferred, from the viewpoint of high graphitization degree and small amount of impurities.

[0212] As artificial graphite, for example, there can be listed substances obtained by heating organic substances such as coal tar pitch, coal-based heavy oil, atmospheric residue, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymers, polyphenylene sulfide, polyphenylene ether, furfuryl alcohol resin, phenol formaldehyde resin, and imide resin to 2500° C. or above for graphitization.

[0213] As a method for spheroidization, a method for spheroidization by applying mechanical energy is preferred because the shape of the particles can be easily controlled.

[0214] Examples of the mechanical energy include impact, compression, friction, shear force, etc. These mechanical energies may be used alone or in combination of two or more.

[0215] The method of applying mechanical energy to spheronize the particles may be any method using a device that applies mechanical energy.

[0216] When the spheroidization treatment is performed, the raw material may be granulated in the presence of other substances. Examples of the other substances include metals capable of alloying with lithium, oxides thereof, and raw coke.

[0217] (Composition of Carbon Material)

[0218] As for the content of carbon material (A), in 100 mass% of the carbon material composition, from the perspective of ensuring the lithium ion diffusion path between particles when pressing the electrode plate and excellent charge and discharge characteristics at high current density, it is preferably 50 mass% or more, more preferably 55 mass% or more, and further preferably 60 mass% or more. From the perspective of excellent rollability when pressing the electrode plate, it is preferably 95 mass% or less, more preferably 90 mass% or less, and further preferably 85 mass% or less.

[0219] As for the content of carbon material (B), in 100 mass% of the carbon material composition, from the perspective of suppressing the side reaction with the electrolyte caused by the increase in the specific surface area of ​​the electrode plate and excellent high-temperature storage characteristics, it is preferably 5 mass% or more, more preferably 10 mass% or more, and further preferably 15 mass% or more. From the perspective of ensuring a proper void structure between particles and excellent rapid charge and discharge characteristics, it is preferably 50 mass% or less, more preferably 45 mass% or less, and further preferably 40 mass% or less.

[0220] For example, the content of the carbon material (A) in the carbon material of the present invention may be 50% by mass to 95% by mass, and the content of the carbon material (B) may be 5% by mass to 50% by mass.

[0221] The carbon material of the present invention may contain other substances in addition to the carbon material (A) and the carbon material (B). Examples of other substances include metals capable of alloying with lithium, oxides thereof, and conductive materials.

[0222] From the viewpoint of not impairing the original function of the carbon material, the content of other substances is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0223] (Method for producing carbon material)

[0224] The method for producing a carbon material of the present invention includes the step of mixing the carbon material (A) and the carbon material (B).

[0225] The mixing method is not particularly limited as long as the carbon material (A) and the carbon material (B) can be mixed into a desired composition.

[0226] The ratio Rd50 of the volume-based average particle size d50 of the carbon material (A) to the volume-based average particle size d50 of the carbon material (B) ([volume-based average particle size d50 of the carbon material (B)] / [volume-based average particle size d50 of the carbon material (A)]) is preferably 0.3 to 1.6, more preferably 0.4 to 1.5, and further preferably 0.5 to 1.4.

[0227] When the ratio Rd50 is within the above range, a uniform lithium ion diffusion path is ensured in the electrode plate, and excellent charge and discharge characteristics at high current density are achieved.

[0228] The ratio RSAp of the specific surface area SAp of the carbon material (A) to the specific surface area SAp of the carbon material (B) ([specific surface area SAp of the carbon material (B)] / [specific surface area SAp of the carbon material (A)]) is preferably 2 to 15, more preferably 3 to 14, and further preferably 4 to 13.

[0229] When the specific RSAp is within the above range, an excessive side reaction with the electrolyte solution is suppressed, and the initial charge and discharge efficiency is excellent.

[0230] The ratio RTap of the tap density of the carbon material (A) to the tap density of the carbon material (B) ([tap density of the carbon material (B)] / [tap density of the carbon material (A)]) is preferably 0.7 to 1.4, more preferably 0.75 to 1.3, and further preferably 0.8 to 1.2.

[0231] When the ratio RTap is within the above range, the slurry stability during electrode plate production is excellent.

[0232] (negative electrode)

[0233] The negative electrode of the present invention comprises a current collector and an active material layer formed on the current collector, wherein the active material layer comprises the carbon material of the present invention. The carbon material of the present invention has an effect as a negative electrode active material.

[0234] The method for manufacturing the negative electrode is not particularly limited as long as an active material layer can be formed on the current collector. From the perspective of low cost and excellent productivity, a method of applying a slurry containing the carbon material of the present invention and a binder resin to the current collector and drying the slurry is preferred. A thickener may also be further added to the slurry.

[0235] Preferably, a slurry containing the carbon material of the present invention and a binder resin is applied to a current collector and dried, and then pressed to increase the density of the active material layer formed on the current collector and increase the battery capacity per unit volume of the active material layer.

[0236] The density of the active material layer is preferably 1.2 g / cm2 from the viewpoint of suppressing the decrease in battery capacity due to an increase in the thickness of the electrode plate. 3 More preferably, 1.5 g / cm 3 The above is preferably 2.0 g / cm2 because the amount of electrolyte retained in the voids is reduced due to the reduction of voids in the electrode plate, the mobility of alkali ions such as lithium ions is reduced, and the decrease in rapid charge and discharge characteristics can be suppressed. 3 Below, more preferably 1.8 g / cm 3 the following.

[0237] (Secondary battery)

[0238] The secondary battery of the present invention includes a positive electrode, the negative electrode of the present invention, and an electrolyte.

[0239] The positive electrode and the negative electrode of the present invention are preferably capable of occluding and releasing lithium ions.

[0240] (positive electrode)

[0241] As the positive electrode, a known positive electrode can be used.

[0242] (Electrolytes)

[0243] As the electrolyte, a known electrolyte can be used.

[0244] (Diaphragm)

[0245] The secondary battery of the present invention preferably has a separator interposed between the positive electrode and the negative electrode.

[0246] As the separator, a known separator can be used.

[0247] (use)

[0248] The carbon material of the present invention can take into account both the discharge load characteristics of the secondary battery and the high-temperature storage recovery rate of the secondary battery, and is therefore suitable for use as an active material for the negative electrode of a secondary battery, and is more suitable for use as an active material for the negative electrode of a non-aqueous secondary battery, and is particularly suitable for use as an active material for the negative electrode of a lithium-ion secondary battery.

[0249] Example

[0250] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to the description of the following examples unless it departs from the gist of the present invention.

[0251] (Method for measuring volume-based average particle size d50)

[0252] 0.01 g of the sample was suspended in 10 mL of a 0.2% by mass aqueous solution of polyoxyethylene sorbitan monolaurate (trade name "Tween 20", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a surfactant, and introduced into a laser diffraction / scattering particle size distribution measuring apparatus (model name "LA-920", manufactured by Horiba, Ltd.), and irradiated with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, and then the volume-based median particle size in the above-mentioned measuring apparatus was measured, and the volume-based median particle size was used as the volume-based average particle size d50.

[0253] (Measurement method of tap density)

[0254] Using a powder density measuring device (model name "Tap Denser KYT-3000", manufactured by Seishin Enterprise Co., Ltd.), the sample was dropped to a diameter of 1.6 cm and a volume capacity of 20 cm. 3 The sample was placed in a cylindrical compaction container and after filling the container, it was compacted 1000 times with a stroke length of 10 mm. The density value calculated based on the volume and mass of the sample at this time was taken as the tap density.

[0255] (Measurement method of powder specific surface area SAp)

[0256] Using a specific surface area measuring device (model name "Macsorb HM Model-1210", manufactured by Mountech Co., Ltd.), the sample was pre-decompressed and dried at 350°C for 15 minutes under nitrogen flow, and then cooled to liquid nitrogen temperature. A nitrogen-helium mixed gas in which the relative pressure of nitrogen relative to atmospheric pressure was accurately adjusted to 0.3 was used to measure the specific surface area by the nitrogen adsorption BET single-point method based on the gas flow method, and the specific surface area was taken as the powder specific surface area SAp.

[0257] (Manufacturing of negative electrode sheet)

[0258] To 50.00±0.02 g of the carbon material obtained in the examples and comparative examples, add 50.00±0.02 g (0.50 g in terms of solid content) of a 1 mass% aqueous solution of sodium carboxymethyl cellulose and 1.00±0.05 g (0.50 g in terms of solid content) of an aqueous dispersion of styrene-butadiene rubber having a weight average molecular weight of 270,000, and stir for 5 minutes using a mixing agitator (manufactured by KEYENCE Corporation), and degas for 30 seconds to obtain a slurry.

[0259] The obtained slurry was dried so that 10.0±0.2 mg / cm 2 The negative electrode material is further rolled to adjust the density of the negative electrode active material layer to 1.3±0.03g / cm 3 ~1.7±0.03g / cm 3 , and obtain the negative electrode sheet (plate).

[0260] (Production of positive electrode)

[0261] 85 mass % of lithium nickel-manganese-cobalt oxide (LiNiMnCoO2) as a positive electrode active material, 10 mass % of acetylene black as a conductive material, and 5 mass % of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methylpyrrolidone to obtain a slurry.

[0262] The obtained slurry has a positive electrode material adhesion of 22.5±0.2mg / cm 2 The positive electrode active material layer was coated on a 15 μm thick aluminum foil as a current collector and dried. Roll pressing was further performed to adjust the density of the positive electrode active material layer to 2.6 ± 0.05 g / cm 3 , and obtain the positive electrode.

[0263] (Manufacturing of sheet-shaped secondary batteries)

[0264] The obtained negative electrode sheet, polyethylene separator, and the obtained positive electrode sheet are stacked in sequence. The obtained stack is wrapped with a cylindrical aluminum laminate film, injected into an electrolyte solution of 1 mol / L LiPF6 dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 30:70), and then vacuum sealed to prepare a sheet-like non-aqueous secondary battery. Further, in order to improve the adhesion, the sheet-like secondary battery is clamped with a glass plate and pressurized.

[0265] (Method for measuring the specific surface area SAe of the electrode plate)

[0266] Using a specific surface area measuring device (model name "Macsorb HM Model-1210", manufactured by Mountech Co., Ltd.), the sample was pre-decompressed and dried at 100°C for 30 minutes under nitrogen circulation, and then cooled to liquid nitrogen temperature. A nitrogen-helium mixed gas with a relative pressure value of nitrogen to atmospheric pressure accurately adjusted to 0.3 was used to measure the specific surface area by the nitrogen adsorption BET single-point method based on the gas flow method, and the specific surface area was taken as the electrode plate specific surface area SAe.

[0267] (Determination method of compression inflection point density)

[0268] In the compression load-negative electrode active material layer density curve obtained when the negative electrode sheet is compressed, the intersection of the tangent line drawn from the low-density area at the zero load point and the tangent line drawn from the area where the density changes linearly in the high-density area is found, and the negative electrode active material layer density corresponding to the load at the obtained intersection is taken as the compression inflection point density.

[0269] As the negative electrode sheet is pressed, the carbon material particles constituting the negative electrode sheet are misaligned, deformed, cracked, etc., and the density of the negative electrode active material layer increases. The pressing inflection point density is an indicator showing changes in various phenomena occurring in these carbon material particles.

[0270] (Measurement method of curvature change rate)

[0271] Two negative electrode sheets obtained by various pressing densities were punched into a disc-shaped negative electrode sheet with a diameter of 12.5 mm, and arranged in a manner that the active material layers face each other. A separator (porous polyethylene film) impregnated with an electrolyte solution of 1 mol / L LiPF6 dissolved in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (volume ratio 30:70) was placed between the opposite negative electrode sheets to produce a 2016 coin-shaped battery.

[0272] The obtained 2016 coin-shaped battery was left to stand at 25°C for 24 hours, and then an impedance response analysis was performed. The impedance response analysis was performed using an impedance analyzer (manufactured by Solartron) at a frequency of 20kHz to 10mHz and a voltage amplitude of 10mV. The ionic resistance R of the active material layer relative to the negative electrode sheet was obtained using the intersection of the 45° straight line in the high-frequency region and the vertical line in the low-frequency region on the Kerr plot. ion The curvature is calculated according to the following formula (5) where the area of ​​the negative electrode sheet is S, the thickness of the active material layer of the negative electrode sheet is L, the conductivity of the electrolyte is σ, and the porosity of the active material layer is ε.

[0273] Curvature = R ion ×(ε / 2×L)×(σ×S)(5)

[0274] Using the calculated curvature, the compacted density is calculated according to the following formula (6): 3 ~1.7g / cm 3 The rate of change of curvature within the range of .

[0275] [Rate of change in curvature] = [Change in curvature] / [Change in pressing density] (6)

[0276] (Method for measuring discharge load characteristics)

[0277] For the obtained sheet-shaped secondary battery, at 25°C, 3 cycles of initial charge and discharge were performed at a voltage range of 4.1V to 3.0V and a current value of 0.2C (the current value for discharging the rated capacity based on the discharge capacity of 1 hour rate in 1 hour is set to 1C, and the same applies hereinafter), and 2 cycles of initial charge and discharge were performed at a voltage range of 4.2V to 3.0V and a current value of 0.2C (when charging, constant voltage charging was further performed at 4.2V for 2.5 hours). Then, constant current charging was performed at a current value of 0.2C to 4.2V, and constant voltage charging was further performed at 4.2V for 2.5 hours, and constant current discharge was performed at 3C to 3.0V, and the ratio of the discharge capacity at 3C discharge to the discharge capacity at 0.2C discharge shown in the following formula (7) was used as the discharge load characteristic (%).

[0278] Discharge load characteristics (%) = ([discharge capacity at 3C discharge] / [discharge capacity at 0.2C discharge]) × 100 (7)

[0279] (Method for determining the recovery rate after high temperature storage)

[0280] For the obtained sheet-shaped secondary battery, at 25°C, initial charge and discharge were performed for 3 cycles at a voltage range of 4.1V to 3.0V and a current value of 0.2C, and initial charge and discharge were performed for 2 cycles at a voltage range of 4.2V to 3.0V and a current value of 0.2C (when charging, constant voltage charging was further performed at 4.2V for 2.5 hours). Furthermore, after charging at a current value of 0.2C until the charge rate (SOC) was 80%, it was stored at 60°C for 2 weeks. Then, it was discharged at a current value of 0.2C, and then charged and discharged at a current value of 0.2C (when charging, constant voltage charging was further performed at 4.2V for 2.5 hours), and the ratio of the discharge capacity after storage to the discharge capacity after initial charge and discharge shown in the following formula (8) was used as the high temperature storage recovery rate (%).

[0281] High temperature storage recovery rate (%) = ([discharge capacity after storage] / [discharge capacity after initial charge and discharge]) × 100 (8)

[0282] [Production Example 1] Production of Carbon Material (A1)

[0283] Flake natural graphite with a volume-based average particle size of 100 μm was crushed to obtain graphite with a volume-based average particle size of 11 μm. 100 parts by mass of the obtained graphite and 12 parts by mass of a granulating agent were mixed, and then spheroidized. The granulating agent was further removed by heat treatment to obtain spheroidized graphite (volume-based average particle size of 16 μm, specific surface area of ​​15 m 2 / g, tap density 0.96g / cm 3 ). The obtained spheroidized graphite is filled into a rubber container, the rubber container is sealed, and after isotropic pressure treatment, it is crushed and classified to obtain spheroidized graphite powder. The obtained spheroidized graphite powder is mixed with asphalt (ash 0.02 mass%, metal impurity content 20 mass ppm, Qi1 mass%) as a precursor of amorphous carbonaceous material, the pressure in the furnace is reduced to less than 10torr, and nitrogen is re-pressurized to atmospheric pressure, and nitrogen is circulated to make the oxygen concentration in the furnace less than 0.01 volume%, and a heat treatment of 1300°C is performed in an inert gas. The obtained burnt product is crushed and classified to obtain a carbon material (A1). The mass ratio of spheroidized graphite to amorphous carbonaceous material in the obtained carbon material (A1) is 1:0.08.

[0284] Table 1 shows the evaluation results of the obtained carbon material (A1).

[0285] [Production Example 2] Production of Carbon Material (A2)

[0286] A carbon material (A2) was obtained in the same manner as in Production Example 1 except that the mixing ratio of the spheroidized graphite powder and the amorphous carbonaceous substance precursor was changed. The mass ratio of the spheroidized graphite to the amorphous carbonaceous substance in the obtained carbon material (A2) was 1:0.095.

[0287] Table 1 shows the evaluation results of the obtained carbon material (A2).

[0288] [Production Example 3] Production of Carbon Material (A3)

[0289] A carbon material (A3) was obtained in the same manner as in Production Example 1 except that the mixing ratio of the spheroidized graphite powder and the amorphous carbonaceous substance precursor was changed. The mass ratio of the spheroidized graphite to the amorphous carbonaceous substance in the obtained carbon material (A3) was 1:0.11.

[0290] Table 1 shows the evaluation results of the obtained carbon material (A3).

[0291] [Production Example 4] Production of Carbon Material (B1)

[0292] A carbon material (B1) was obtained by spheroidizing flaky natural graphite having a volume-based average particle size of 100 μm.

[0293] Table 2 shows the evaluation results of the obtained carbon material (B1).

[0294] [Production Example 5] Production of Carbon Material (B2)

[0295] A carbon material (B2) was obtained by spheroidizing flaky natural graphite having a volume-based average particle size of 100 μm.

[0296] Table 2 shows the evaluation results of the obtained carbon material (B2).

[0297] [Production Example 6] Production of Carbon Material (B3)

[0298] A carbon material (B3) was obtained by spheroidizing flaky natural graphite having a volume-based average particle size of 100 μm.

[0299] Table 2 shows the evaluation results of the obtained carbon material (B3).

[0300] [Example 1]

[0301] A carbon material was obtained by mixing 80% by mass of the carbon material (A1) and 20% by mass of the carbon material (B2).

[0302] Table 4 shows the evaluation results of the obtained carbon materials.

[0303] [Examples 2 to 4]

[0304] Except having changed the type and content of the carbon material as shown in Table 3, the same operation as in Example 1 was carried out to obtain a carbon material.

[0305] Table 4 shows the evaluation results of the obtained carbon materials.

[0306] [Comparative Examples 1 to 6]

[0307] Except having changed the type and content of the carbon material as shown in Table 3, the same operation as in Example 1 was carried out to obtain a carbon material.

[0308] Table 4 shows the evaluation results of the obtained carbon materials.

[0309] [Table 1]

[0310] Table 1

[0311]

[0312] [Table 2]

[0313] Table 2

[0314]

[0315] [Table 3]

[0316] Table 3

[0317]

[0318] [Table 4]

[0319] Table 4

[0320]

[0321] As can be seen from Table 4, the carbon materials of Examples 1 to 4, which are carbon materials of the present invention, have excellent discharge load characteristics and high-temperature storage recovery rates of secondary batteries. On the other hand, the carbon materials of Comparative Examples 1 to 3, which are carbon materials that do not satisfy the necessary conditions of the present invention, have poor high-temperature storage recovery rates of secondary batteries. In addition, similarly, the carbon materials of Comparative Examples 4 to 6, which are carbon materials that do not satisfy the necessary conditions of the present invention, have poor discharge load characteristics and high-temperature storage recovery rates of secondary batteries. It can be considered that the reason for this result is that by making the carbon material satisfy both formula (1) and formula (2), or by containing a carbon material (A) satisfying formula (3) and a carbon material (B) satisfying formula (4), the increase in the specific surface area of ​​the electrode during high-density pressing is suppressed, and the void structure in the electrode required for lithium ion diffusion is well maintained.

[0322] Above, various embodiments have been described, but the present invention is certainly not limited to such examples. Those skilled in the art can obviously think of various variations or modifications within the scope described in the claims, and it can be understood that they certainly also belong to the technical scope of the present invention. In addition, within the scope of not departing from the gist of the invention, the various constituent elements in the above-mentioned embodiments can also be arbitrarily combined.

[0323] It should be noted that the present application is based on the Japanese patent application (Japanese Patent Application No. 2022-124174) filed on August 3, 2022, the contents of which are incorporated herein by reference.

[0324] Industrial Applicability

[0325] The carbon material of the present invention can take into account both the discharge load characteristics of the secondary battery and the high-temperature storage recovery rate of the secondary battery, and is therefore suitable for use as an active material for the negative electrode of a secondary battery, and is more suitable for use as an active material for the negative electrode of a non-aqueous secondary battery, and is particularly suitable for use as an active material for the negative electrode of a lithium-ion secondary battery.

Claims

1. A carbon material that satisfies the following formula (1) and the following formula (2), 0.1≤SAe / SAp≤1.2 (1) 1≤α≤10 (2) In formula (1), SAp is the specific surface area of ​​the powder form of the carbon material, SAe is the specific surface area at the inflection point of load-density when the carbon material is pressed into a plate, and in formula (2), α is the specific surface area of ​​the carbon material at a pressed density of 1.3 g / cm 3 ~1.7g / cm 3 The rate of change of curvature within a range of .

2. The carbon material according to claim 1, wherein SAp is 1.5m 2 / g~4.5m 2 / g.

3. The carbon material according to claim 1, wherein SAe: 0.5m 2 / g~3.5m 2 / g.

4. The carbon material according to claim 1, wherein The volume-based average particle size is 5 μm to 25 μm.

5. A carbon material comprising a carbon material (A) satisfying the following formula (3) and a carbon material (B) satisfying the following formula (4), 0.1≤α1≤6 (3) 8≤α2≤20 (4) In formula (3), α1 is the carbon material at a compacted density of 1.3 g / cm 3 ~1.7g / cm 3 The change rate of curvature in the range of , where α2 is the carbon material at a compact density of 1.3 g / cm 3 ~1.7g / cm 3 The rate of change of curvature within a range of .

6. The carbon material according to claim 5, wherein The ratio Rd50 of the volume-based average particle size of the carbon material (A) to the volume-based average particle size of the carbon material (B) is 0.3 to 1.

6.

7. The carbon material according to claim 5, wherein The ratio RSAp of the specific surface area of ​​the carbon material (A) to the specific surface area of ​​the carbon material (B) is 2-15.

8. The carbon material according to claim 5, wherein The ratio RTap of the tap density of the carbon material (A) to the tap density of the carbon material (B) is 0.7 to 1.

4.

9. The carbon material according to claim 5, wherein The content of the carbon material (A) is 50% by mass to 95% by mass, and the content of the carbon material (B) is 5% by mass to 50% by mass. 10 . The method for producing a carbon material according to claim 5 , comprising the step of mixing the carbon material (A) and the carbon material (B).

11. A negative electrode comprising a current collector and an active material layer formed on the current collector, The active material layer contains the carbon material according to any one of claims 1 to 9.

12. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein: The negative electrode is the negative electrode according to claim 11.

Citation Information

Patent Citations

  • Measuring device

    JP2022124174A

  • Starting material of negative electrode material for nonaqueous secondary batteries, negative electrode material for nonaqueous secondary batteries, negative electrode for nonaqueous secondary batteries, and nonaqueous secondary battery

    WO2020196914A1